Evaluasi Produksi Overburden Menggunakan System Six Big Losses pada Pit K1 Mahakam PT. Insani Baraperkasa Kecamatan Loa Janan Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur - Nurhamidah, Nurhamidah; Harjuni Hasan; Ardhan Ismail (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Overburden removal is a critical phase in coal mining operations, as it directly affects production continuity and operational efficiency. However, production realization often deviates from the mine plan due to various operational constraints. This study, conducted at Pit K1 Mahakam of PT. Insani Baraperkasa, evaluates the causes of underachievement in overburden stripping targets using the Six Big Losses framework, which classifies inefficiencies into Breakdown Losses, Setup and Adjustment Losses, Idling and Minor Stops, Reduced Speed Losses, Process Defect Losses, and Reduced Yield Losses. The analysis revealed that the dominant losses were Reduced Speed Losses (26%) and Setup and Adjustment Losses (10%), primarily caused by disposal congestion, shift changes, and repairs at the loading and disposal areas. Minor contributions were found from idling (3%), production losses (5%), while breakdown losses showed negligible impact. These factors led to increased standby time and reduced equipment cycle effectiveness. Improvement strategies are recommended through optimized disposal allocation, reduction of waiting time, and stricter control of external operational disruptions to enhance stripping efficiency and achieve production targets.